Territorial Economic Data viewer: An introduction to the industrial module - Ilias Kostarakos; Anabela Marques Santos (European Commission, Joint Research Centre (JRC), 2025)
This paper introduces the new module of the European Commission's Territorial Economic Data viewer (TEDv) namely, the Industrial Module. The aim is to present the data sources and the methodological approach employed to generate the various dashboards included in this new module. Its usefulness is exhibited via an extensive analysis of the current states of the economic sectors and industrial ecosystems identified as the most prominent ones.
Keywords: 330